Proceedings of the Proceedings of the 7th Mathematics, Science, and Computer Science Education International Seminar, MSCEIS 20 2020
DOI: 10.4108/eai.12-10-2019.2296532
|View full text |Cite
|
Sign up to set email alerts
|

An Integration of National Identity towards Single Identity Number with Blockchain

Abstract: The lack of coordination in the integration of information systems between government agencies that issue identity numbers causes replication and redundancy of population information data. Another problem is the emergence of citizens' concerns over data integrity and security due to national identification records is also used by the private sector. In this paper, one of the solutions offered to overcome the above problem is to build an integrated national identification database system between government agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Based on the results of functional testing of the system, it can be concluded that the prototype of this system can work according to the functional requirements that have been defined. In other words, this research has succeeded in complementing the previous research [19] by developing and implementing the model design proposed in the previous research in Hyperledger Fabric. This research also offers the use of population data by user institutions so that it is equipped with access restrictions that user institutions can carry out.…”
Section: E Functional Testingmentioning
confidence: 76%
See 2 more Smart Citations
“…Based on the results of functional testing of the system, it can be concluded that the prototype of this system can work according to the functional requirements that have been defined. In other words, this research has succeeded in complementing the previous research [19] by developing and implementing the model design proposed in the previous research in Hyperledger Fabric. This research also offers the use of population data by user institutions so that it is equipped with access restrictions that user institutions can carry out.…”
Section: E Functional Testingmentioning
confidence: 76%
“…Adapting to Indonesian conditions, Fathiyana et al in 2020 [19] proposed a model design for an integrated national identification database system between government agencies by applying the Single Identity Number (SIN) concept using blockchain technology. The blockchain design consists of three peers, namely civil registration, government agencies, and the private sector.…”
Section: A Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Robles et al [38] combined the building features of blockchain technology to initiate and utilize a customer-focused data management system in AMI. Since blockchain is a decentralized public digital ledger for recording transactions that cannot be changed without changing all the subsequent blocks and the consensus of the network, access control, integrity, and authentication of the involved data were therefore guaranteed via blockchain [39,40] PUFs get easily denatured/altered in the presence of extreme temperatures [27] 2…”
Section: Privacy and Security Vulnerabilities Of Amimentioning
confidence: 99%